HUBUNGAN AKTIFITAS BERNYANYI YANG DILAKUKAN SUPORTER FUTSAL DENGAN GANGGUAN SUARA DI SMAN 1 SURAKARTA - Aulia, Rezekika; Gunawan, Gunawan (Medical Journal of Nusantara, 2024)
Background: Voice disorder often occur due to misuse of the voice. Anyone, whether male or female, who uses their voice excessively can make their voice problems worse by shouting too much and talking too loundy. Some jobs are very susceptible to voice problems, including football coaches, singers, me, and supporters. However, supporters' understanding of sound disorders is very low. Objectives: This study aims to determine the relationship between singing activities and voice disorders in futsal supporters at SMAN 1 Surakarta. Methods: This research took futsal supporter respondents at SMAN 1 Surakarta. The number of respondents studied was 52 respondents with data collection using Purposive sampling and the respondents filled in the questionnaire provided. Results: The number of respondents who did not have voice problems was 67.3%. while those who experienced mild disorders were 32.7%. The results of the Kendall Tau test concluded that the value of p = 0.001, meaning that Ha (Alternative Hypothesis) was accepted because the value of ρ < 0.05 indicated that there was an active relationship between supporters of singing activities and noise disturbance at that time. SMAN 1 Surakarta. Meanwhile, the correlation coefficient (r) value obtained was 0.406, indicating that the strength of the relationship between supporters of singing activities and voice disorders was in the "Medium" category. The direction of correlation between variables is positive, meaning that the two variables have a unidirectional relationship, where the value of one variable increases as the value of the other variable increases. Conclusion: There is a relationship between the singing activities of futsal sapporters and voice disorders at SMAN 1 Surakarta.